Pharmacokinetics/pharmacodynamics of antibiotics with different protein binding rates in hemodialysis - SHEN Yue; WANG Yu; XU Jingyi; CHEN Yuancheng; ZHANG Jing; DING Feng (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To evaluate the clearance and pharmacokinetics/pharmacodynamics (PK/PD) of antibiotics from the perspective of protein binding rates in critically ill patients undergoing intermittent hemodialysis (IHD), in order to explore the association between protein binding rate and dialysis clearance of antibiotics, and to provide theoretical basis for developing antibiotic dosing regimens during hemodialysis.Methods·Nineteen patients undergone low-flux hemodialysis and received antibiotic therapy at the Department of Nephrology, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, were enrolled and divided into the meropenem group (n=7), the vancomycin group (n=5) and the ceftriaxone group (n=7) according to the type of antibiotics. A liquid chromatography with tandem mass spectrometry (LC-MS/MS) method was established to detect meropenem, vancomycin, and ceftriaxone in human plasma/serum and dialysate. A two-compartment pharmacokinetic model was established using MATLAB. Instantaneous and total dialysis clearance rates were calculated, and PK/PD parameters were analyzed.Results·No significant differences were found in the clinical characteristics of subjects among the three groups. The dialysis clearance rates were as follows: meropenem group (5.14‒5.97 L/h) > vancomycin group (2.87‒3.77 L/h)> ceftriaxone group (1.21‒1.90 L/h), with statistically significant differences (P<0.001). All three antibiotics showed good fit in the two-compartment pharmacokinetic model with a dialysate chamber (fval%<2), and the calculated PK/PD parameters were consistent with previous literature. For meropenem, the fraction of time that the free drug concentration remained above the minimal inhibitory concentration (%fT>MIC) values were 95.2%, 60.8% and 32.4% at minimal inhibitory concentration (MIC) values of 2, 8 and 16 μg/mL, respectively. For ceftriaxone (free concentration), the %fT>MIC values were all above 45.0% at MICs of 0.25, 4 and 16 μg/mL. For vancomycin, only 14.0% of the trough concentrations reached the target range of 15‒20 mg/L.Conclusion·The three antibiotics are well described by the two-compartment model. The plasma protein binding rate has a significant effect on the dialysis clearance of antibiotics in low-flux IHD, with higher protein binding associated with lower clearance. The regimens of meropenem (0.5 g/d) and ceftriaxone (2.0 g/d) are generally effective among patients undergoing low-flux IHD, while the vancomycin regimen with a loading dose of 1.0 g and a maintenance dose of 0.5 g/2 d carries a risk of treatment failure.